Stepping Towards Sustainable Leadership: Analysis of Leadership Practices In The Mining Industry In Supporting The Achievement of Sustainable Development Goals - Wijaya, Sumadi; Pratomo, Luki Adiati (Pelopor Publikasi Akademika, 2024)
This research aims to fill the research gap by analyzing sustainable leadership practices in the mining industry, expanding the understanding from previous sustainable leadership literature. The focus is to provide a deep understanding of the role of sustainable leadership in supporting the Sustainable Development Goals (SDGs). Qualitative methods are employed to comprehend social phenomena through the collection and analysis of descriptive and non-numeric data. The study explores